2020
DOI: 10.3389/fevo.2020.567049
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Transcriptomic Differentiation of Independent Invasions of the Pacific Oyster Crassostrea gigas

Abstract: Upon colonizing new habitats, invasive species face a series of new selection pressures as a result of changing abiotic conditions and novel biotic interactions with native species. These new selection pressures can be accommodated by different mechanisms that act on different levels and across different time scales: (1) By changing transcriptomic profiles, species can react by plasticity within individual physiological limitations. (2) Invasive populations can adapt by fixing beneficial genetic variants in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…In a rare comparison of sequence variation and expression variation, a study of two independent invasions of the Pacific Oyster (Crassostrea gigas) into the North Sea found little overlap between differentially expressed genes and outlier loci. This suggested that differential gene expression did not necessarily correlate with changes in allele frequencies (Wegner et al, 2020). However, as is common in ecological genomics, this study suffered from limited annotation of the transcriptome and limited coverage of the genome (using reduced representation RADseq).…”
Section: Discoveries and Limitations Of Genomic Studies Of Diverse Invasive Speciesmentioning
confidence: 99%
“…In a rare comparison of sequence variation and expression variation, a study of two independent invasions of the Pacific Oyster (Crassostrea gigas) into the North Sea found little overlap between differentially expressed genes and outlier loci. This suggested that differential gene expression did not necessarily correlate with changes in allele frequencies (Wegner et al, 2020). However, as is common in ecological genomics, this study suffered from limited annotation of the transcriptome and limited coverage of the genome (using reduced representation RADseq).…”
Section: Discoveries and Limitations Of Genomic Studies Of Diverse Invasive Speciesmentioning
confidence: 99%